2000
DOI: 10.1523/jneurosci.20-19-07268.2000
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin Expression Stimulates Endosomal–Lysosomal Activity, Endosome Tubulation, and Autophagy

Abstract: An expansion of polyglutamines in the N terminus of huntingtin causes Huntington's disease (HD) and results in the accrual of mutant protein in the nucleus and cytoplasm of affected neurons. How mutant huntingtin causes neurons to die is unclear, but some recent observations suggest that an autophagic process may occur. We showed previously that huntingtin markedly accumulates in endosomal-lysosomal organelles of affected HD neurons and, when exogenously expressed in clonal striatal neurons, huntingtin appears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
380
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(418 citation statements)
references
References 60 publications
22
380
4
Order By: Relevance
“…These findings are coincident with the reduction of lysosomal activity observed in mhtt cells. Interestingly, we observed that overexpression of truncated forms of mhtt, such as exon1-103Q-htt, stimulated post-Golgi transport of Lamp-1 and also increased the labeling of cathepsin D in enlarged LysoTrackerpositive structures (Supplemental Figure 5), which is in agreement with a previous study (Kegel et al, 2000). This effect could be explained by several protein interactions that are lost in the case of shorter fragments of htt.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are coincident with the reduction of lysosomal activity observed in mhtt cells. Interestingly, we observed that overexpression of truncated forms of mhtt, such as exon1-103Q-htt, stimulated post-Golgi transport of Lamp-1 and also increased the labeling of cathepsin D in enlarged LysoTrackerpositive structures (Supplemental Figure 5), which is in agreement with a previous study (Kegel et al, 2000). This effect could be explained by several protein interactions that are lost in the case of shorter fragments of htt.…”
Section: Discussionsupporting
confidence: 92%
“…Polyglutamine expansion induces autophagy mTOR inhibition induces autophagy, which has been previously reported in brains of individuals with Huntington disease, in transgenic mice expressing mutant huntingtin fragments and in a cell model of Huntington disease, using morphological criteria 23,24 . It has been difficult to differentiate autophagosomes from other vesicles in the absence of specific autophagosome markers.…”
Section: Decreased Mtor Activity In Other Polyglutamine Diseasesmentioning
confidence: 55%
“…mTOR was diffusely distributed in untransfected cells, in cells expressing wild-type protein (Gln 23 ; Fig. 1a) and in cells expressing mutant protein (Gln 74 ) without aggregates but colocalized with both cytoplasmic and nuclear aggregates in >98% of mutant cells with aggregates ( Fig.…”
Section: Results Mtor Is Sequestered Into Huntingtin Aggregatesmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, it is advisable to take the term 'autophagic cell death' to mean cell death occurring with associated autophagy rather than as a result of autophagy. The role of autophagy in disease is not well understood; it appears to play a protective role in the progression of neurodegenerative diseases and muscular disorders and provide protection from infections [123][124][125] , but contributes to the pathology of other diseases such as…”
Section: Autophagymentioning
confidence: 99%